2018
DOI: 10.1007/s13659-018-0162-1
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Research on Artemisinin and Its Bioactive Derivatives

Abstract: Cancer is the leading cause of human death which seriously threatens human life. The antimalarial drug artemisinin and its derivatives have been discovered with considerable anticancer properties. Simultaneously, a variety of target-selective artemisinin-related compounds with high efficiency have been discovered. Many researches indicated that artemisinin-related compounds have cytotoxic effects against a variety of cancer cells through pleiotropic effects, including inhibiting the proliferation of tumor cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 165 publications
(180 reference statements)
0
43
0
Order By: Relevance
“…In addition, we can see that scaffold 11 is 1,2,4‐trioxane endoperoxides, and the representative compound of this scaffold is artemisinin, famous for its antimalarial bioactivity. No molecule in the training set contains this scaffold, and the twelve molecules of this scaffold were all predicted as antineoplastic, which was promisingly supported by recent experimental studies of the antineoplastic bioactivity of artemisinin derivatives [29–30] . However, the antitumor activity in the literature was only a molecular level activity and cannot be directly considered as an indication.…”
Section: Resultsmentioning
confidence: 57%
“…In addition, we can see that scaffold 11 is 1,2,4‐trioxane endoperoxides, and the representative compound of this scaffold is artemisinin, famous for its antimalarial bioactivity. No molecule in the training set contains this scaffold, and the twelve molecules of this scaffold were all predicted as antineoplastic, which was promisingly supported by recent experimental studies of the antineoplastic bioactivity of artemisinin derivatives [29–30] . However, the antitumor activity in the literature was only a molecular level activity and cannot be directly considered as an indication.…”
Section: Resultsmentioning
confidence: 57%
“…In cancer, the therapeutic strategy relies on the fact that cancer cells contain significantly more intracellular free iron than normal cells making them more sensitive to artemisinin [ 14 ]. It has been shown that artemisinin and its analogs selectively cause apoptosis in multiple cancer cell lines [ 10 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Moreover, artemisinin loaded with transferrin in liposomes demonstrated anticancer activity [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that phenylhydrazine (PHZ) causes oxidative stress within erythrocytes resulting in oxidation of oxyhemoglobin leading to the formation of metHb, which is subsequently converted into irreversible hemichromes (HMCs) that lead to the precipitation of denatured hemoglobin in the form of Heinz bodies [ 29 ]. Methemoglobin has also been reported as a redox-responsive nanocarrier to trigger the in situ anticancer ability of artemisinin [ 22 ]). Li et al demonstrated that the encapsulation of ART into the metHb nanocarrier activated iron-mediated free radical generation and, consequently, triggered an elevated in situ tumor-reducing capacity, proving the promising anticancer ability of the metHb-ART complex.…”
Section: Introductionmentioning
confidence: 99%
“…Using an alkyne‐tagged artemisinin analog linked to fluorescent reporters or biotin to monitor drug activation, we observed that artemisinin interacts with a wide range of protein targets, suggesting a promiscuous mechanism of action. In addition to artemisinin monomers, recent research on the mechanism of artemisinin polymers is also important, and the relationship between the artemisinin polymer structure and activity still needs to be investigated.…”
Section: Introductionmentioning
confidence: 99%